2011
DOI: 10.1111/j.1442-200x.2010.03203.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of low‐dose and high‐dose cosyntropin stimulation testing in children

Abstract: LD cosyntropin stimulation testing results should be interpreted cautiously when used alone to prevent unnecessary long-term treatment. Using a lower cut-off for LD (≥14 µg/dL) seems to avoid false positive results and still detects most cases of impaired HPAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Secondary/tertiary adrenal insuffi ciency was diagnosed with suboptimal response to ACTH stimulation test as described elsewhere (16) .…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…Secondary/tertiary adrenal insuffi ciency was diagnosed with suboptimal response to ACTH stimulation test as described elsewhere (16) .…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…e false-negative results may lead to premature discontinuation of cortisol replacement, which increase the risk of adrenal insufficiency in stress condition. We adopted the LDT in the study as it gives comparable and more accurate results than the HDT dose [15,[17][18][19]. What is more, it is reported that measuring cortisol at both 30 and 60 minutes following the ACTH stimulation test may be necessary to avoid overdiagnosing CAI [20].…”
Section: Discussionmentioning
confidence: 99%
“…21 Additional studies suggest setting a lower level of 14 mcg/dL to avoid false positive results and to increase screening sensitivity. 24 This patient did not have a stimulation test and instead demonstrated low morning cortisol levels with a markedly elevated ACTH level (also diagnostic for AD).…”
Section: Diagnosis Of Apsmentioning
confidence: 91%